let f(x)=2x^2+6 and g(x)=-4x+1
Thank you for the opportunity to help you with your question!
(f – g)(x) = f(x) – g(x)
= 2x^2+6 - ( -4x+1 )
= 2x^2+6 + 4x - 1
= 2x^2 + 4x + 5
(f-g)(-3) = 2(-3)^2 + 4(-3) + 5 ( substitute -3 in place of x)
= 2*9 -12 +5
= 18 - 12 +5
AWESOME! Thank you so much for explaining how to do it!
you are welcome
if you have any doubts in this question or any new question..please assign me as your tutor
thank you for working with me.
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?